Increased numbers of T lymphocytes with gamma delta-positive antigen receptors in a subgroup of individuals with pulmonary sarcoidosis. - Balbi, B (1990)
Individuals with sarcoidosis were evaluated for preferential usage of T cells with the gamma delta-positive (+) type of T cell antigen receptor. Compared with normal subjects (n = 19), the group with sarcoidosis had increased numbers of CD3+ alpha beta-negative (-) T cells in the blood (normal, 58 +/- 12 cells/microliters; sarcoid, 192 +/- 45 cells/microliters, P less than 0.05) and in the epithelial lining fluid of the lung (normal, 78 14 cells/microliters; sarcoid, 240 +/- 60 cells/microliters, P less than 0.04) and a concomitant elevated number of blood and lung CD3+ gamma delta+ T cells, owing to a striking increase in the number of CD3+ gamma delta+ T cells in a subgroup (7 of 20) of sarcoid individuals. The elevated numbers of sarcoid blood gamma delta+ T lymphocytes were mostly Ti gamma A+ and delta TCS1-, a pattern also seen in normal individuals, consistent with the majority of gamma delta+ T cells expressing one gamma-chain variable region, V gamma 9. The observation of an increase in the total gamma delta+ T cell numbers in a sarcoid subgroup suggests that various specific stimuli may trigger the expansion of different T cell subpopulations within different groups of individuals with sarcoidosis.